MENGATASI KESULITAN MEMBACA DAN BELAJAR HURUF ABJAD PADA ANAK DENGAN PENGGUNAAN MEDIA SANDPAPER LETTER DALAM METODE MONTESSORI - Anjar, Diaz; Amartya , Sofia Laretna; Reno, Hacika Cinan; Anugrahana, Andri (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research aims to determine the effect of using sandpaper letter learning media using the Montessori method in overcoming difficulties in reading and learning letters in children aged 3 to 6 years. The method used is descriptive qualitative, which produces data in descriptive form. Which is in the form of written information from the subject who has been observed. The research subjects were 3 children aged 3 to 6 years. This research involves the stages of preparation, implementation and data analysis. The data analysis method used is critical analysis techniques, and data collection techniques used include interviews, observation and documentation. The research results obtained show that the use of sandpaper letter media in the Montessori method has an effect in overcoming difficulties in reading and learning letters in children aged 3 to 6 years. This highlights the importance of using learning media that is appropriate to the difficulties faced by children in reading.